Characterization of Campylobacter spp. Strains Isolated From Wild Birds in Turkey - Kürekci, Cemil; Sakin, Fatih; Epping, Lennard; Knüver, Marie-Theres; Semmler, Torsten; Stingl, Kerstin (Frontiers in Microbiology, 2021)
Turkey is an important stopover site for many migrating birds between Europe, Asia and Africa. Campylobacter spp. are frequently found in wildlife, in particular waterfowl, and distinct strains are disseminated within this reservoir. In this study, 183 wild birds of hunting areas in Turkey were collected and thermophilic Campylobacter spp. from cloacal swabs were isolated at a prevalence of 5.2% from song thrushes (6/116) and 93 % from Eurasian coots (41/44). After PCR species differentiation and flaA restriction profiles determination, C. jejuni and C. coli strains were further investigated by whole genome sequencing. PCR target amplification of the ceuE gene, commonly used for C. coli species-identification was inefficient and even hampered in one isolate. A close look on the ceuE sequence revealed that various mismatches in the ceuE oligo annealing sites caused less efficient diagnostic detection. All C. coli isolates belonged to the environmental clade II and clade III, for which thirty-six novel MLST types were identified. Further single nucleotide polymorphism (SNP) analysis showed a high genomic divergence between the C. coli isolates. High variability was also implicated for putative plasmid-located genes detected in 51% of the C. coli isolates. Distinct gene variants in clades II and III C. coli were identified by a k-mer analysis. After substracting k-mers in common with C. coli clade I database, 11 and 35 distinct genes were identified in clades II and III isolates, mainly involved in surface structures and modifications as well as signal transduction, suggesting niche adaptation of C. coli strains in wild birds. All strains were susceptible against (fluoro-)quinolones, erythromycin, tetracycline, gentamicin and only one isolate was resistant against streptomycin, suggesting that the sensitive phenotype was due to absence of selective pressure and niche separation in wild birds in Turkey. We conclude that Campylobacter spp. isolates from wildlife and environmental sources are still scarce in the databases and that there is a need for more studies on thermophilic Campylobacter spp. from different places all over the world in order to complement our understanding on dissemination and adaptation to distinct niches of this global food-borne pathogen.